Integrated skill-sprint model for the company's human capital development - Protasenko, O. (Запоріжжя: ТДАТУ, 2025)
Today, society lives in the era of the fourth industrial revolution, where disruptive technologies – artificial intelligence, the Internet of Things and machine learning – have become integral to business reality. In this paradigm, strategic advantage depends less on capital or technology and more on human capital. The rapid pace of change shortens the life cycle of professional skills to five years, and in IT – to two or three. Traditional approaches based on long-term planning and standardized programs lose relevance, as they are too slow and often lead to outdated training and wasted investments. The key problem for organisations is the growing gap between digital economy requirements and existing corporate development systems [1, 2]. Business needs adaptive specialists with deep expertise and interdisciplinary skills – technical, cognitive, and soft – able to learn quickly, work in cross-functional teams, and solve complex problems. This requires a shift from passive knowledge consumption to active, flexible, and result-oriented learning models.
Keywords: skill-sprint; capital development